2020
DOI: 10.34172/jsums.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger along with exercise training on serum levels of ALT and AST liver enzymes and malondialdehyde and the activity of liver tissue superoxide dismutase in male Wistar rats

Abstract: Background and aims: The purpose of this study was to examine the effect of 2 months of endurance training (ET) along with ginger consumption on the serum levels of liver enzymes (ALT and AST), enzymatic activity of superoxide dismutase, and malondialdehyde (MDA) in liver tissue in male Wistar rats. Material and Methods: 40 adult male Wistar rats were randomly divided into 5 groups according to the weight as follows: control (n=8), sham (n=8), ET (n=8), ginger (n=8), and ET + ginger (n=8). The training protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The most sensitive and profitable diagnostic enzymes of the liver status are aminotransferases including aspartate aminotransferase (AST) and alanine aminotransferase (ALT) Generally, certain amounts of these enzymes are produced by liver cells, yet after liver damage, the liver cells increase the secretion of the enzymes and their plasma levels, (Terohid et al, 2015).The incidence of oxidative stress in the body has other negative effects, such as muscle fatigue, early restlessness impaired, decreased immune function, and muscle oxidation (Bloomer and Goldfarb, 2004).The results showed that 60 days of training protocol had slight alteration effect on serum levels of ALT and AST on +ve control and corn silk feeding groups exposed to exhaustive test. The lack of alteration is inconsistent with the findings of Kim et al,(2007) and Ghasemnian et al,(2020).Acute strenuous exercise induces oxidative stress and/or tissue damage in several tissues including skeletal muscle, liver, and kidney (Suzuki et al, 2003, Aoi et al .,2004,Suzuki ,2018. Davies et al, 1982 reported that exhaustive exercise increases reactive oxygen species (ROS) generation and induces tissue damage in liver and skeletal muscle.…”
Section: Discussionmentioning
confidence: 96%
“…The most sensitive and profitable diagnostic enzymes of the liver status are aminotransferases including aspartate aminotransferase (AST) and alanine aminotransferase (ALT) Generally, certain amounts of these enzymes are produced by liver cells, yet after liver damage, the liver cells increase the secretion of the enzymes and their plasma levels, (Terohid et al, 2015).The incidence of oxidative stress in the body has other negative effects, such as muscle fatigue, early restlessness impaired, decreased immune function, and muscle oxidation (Bloomer and Goldfarb, 2004).The results showed that 60 days of training protocol had slight alteration effect on serum levels of ALT and AST on +ve control and corn silk feeding groups exposed to exhaustive test. The lack of alteration is inconsistent with the findings of Kim et al,(2007) and Ghasemnian et al,(2020).Acute strenuous exercise induces oxidative stress and/or tissue damage in several tissues including skeletal muscle, liver, and kidney (Suzuki et al, 2003, Aoi et al .,2004,Suzuki ,2018. Davies et al, 1982 reported that exhaustive exercise increases reactive oxygen species (ROS) generation and induces tissue damage in liver and skeletal muscle.…”
Section: Discussionmentioning
confidence: 96%